HEGEMONI DALAM NOVEL 1998 KARYA RATNA INDRASWARI IBRAHIM: PERSPEKTIF ANTONIO GRAMSCI - Radin, Nur Indahsari; Mahmudah, Mahmudah; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to examine the discourse of hegemony in the 1998 novel by Ratna Indraswari Ibrahim using Antonio Gramsci's theory of hegemony. The research focuses on two aspects, namely forms of cultural hegemony and the theoretical concept of hegemony. This type of research is qualitative descriptive research. Data were collected through a technical literature study. The results of the research provide an overview of the form of hegemony of Javanese culture implemented by President Soeharto for thirty years. Apart from that, cultural hegemony is also illustrated through the attitudes and views of the Putri character's family regarding the culture and customs of the descendants of a wedana. The theoretical concept of hegemony contained in the novel is described by four concepts, namely, character, ideology, popular belief, the role of intellectuals, and the role of the state.